2016
DOI: 10.1088/0957-4484/27/7/075606
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Pδ-layer in SiO2by monolayer doping

Abstract: Achieving the required control of dopant distribution and selectivity for nanostructured semiconducting building block is a key issue for a large variety of applications. A promising strategy is monolayer doping (MLD), which consists in the creation of a well-ordered monolayer of dopant-containing molecules bonded to the surface of the substrate. In this work, we synthesize a P δ-layer embedded in a SiO2 matrix by MLD. Using a multi-technique approach based on time of flight secondary ion mass spectrometry (To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…Actually surface density of dopant-containing molecules in MLD is intrinsically limited by steric hindrance effects and availability of reactive sites on the pristine surface. For P-containing molecules, a maximum areal dose of ∼8 × 10 14 atoms/cm 2 was reported. , This value is close to the maximum number of P impurities that can be accommodated on silicon surfaces considering the density of available reactive sites. , Slightly lower areal doses of dopant impurities were obtained using bulkier dopant-containing molecules with different chemical composition due to steric hindrance effects . However, optimization of the grafting process is required for each specific dopant-containing molecule to account for its thermal stability and specific chemical interaction with the target substrate.…”
mentioning
confidence: 81%
“…Actually surface density of dopant-containing molecules in MLD is intrinsically limited by steric hindrance effects and availability of reactive sites on the pristine surface. For P-containing molecules, a maximum areal dose of ∼8 × 10 14 atoms/cm 2 was reported. , This value is close to the maximum number of P impurities that can be accommodated on silicon surfaces considering the density of available reactive sites. , Slightly lower areal doses of dopant impurities were obtained using bulkier dopant-containing molecules with different chemical composition due to steric hindrance effects . However, optimization of the grafting process is required for each specific dopant-containing molecule to account for its thermal stability and specific chemical interaction with the target substrate.…”
mentioning
confidence: 81%
“…In this technique, dopant-carrying molecules are first covalently immobilized on the semiconductor surface via surface reactions. Due to surface self-limiting property, the areal dose of dopant molecules can be modulated by varying reaction temperature 6 , reaction time 6 , molecule size 7 , and the composition of the molecules 8 , 9 . Subsequently, the dopants are driven into the semiconductor bulk and activated by thermal annealing.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of silicon doping the most prominent issue is the silicon oxide formation at the surface. Phosphorus diffuses through silicon oxide significantly slower than through silicon [1617]. Although it has been shown that hydrogen-terminated silicon re-oxidizes relatively slowly when stored at room temperature in air [3], the elevated temperatures required for MLD processing carried out in the liquid phase enhances this re-oxidation.…”
Section: Resultsmentioning
confidence: 99%